Epigenetic-Mediated Downregulation of Zinc Finger Protein 671 (ZNF671) Predicts Poor Prognosis in Multiple Solid Tumors - Jian Zhang; Jian Zhang; Ziqi Zheng; Jieling Zheng; Tao Xie; Tao Xie; Yunhong Tian; Yunhong Tian; Rong Li; Rong Li; Baiyao Wang; Baiyao Wang; et al. (Frontiers in Oncology, 2019)
Zinc finger protein 671 (ZNF671) is a member of the largest transcription factor family in the human genome. However, the methylation status, expression, and prognostic role of ZNF671 in solid tumors remain unclear. The aim of this study was to explore the relationship between ZNF671 and the prognosis of patients with solid tumors. We performed a pan-cancer analysis of the methylation status and mRNA and protein expression of ZNF671 using The Cancer Genome Atlas (TCGA) database and the Human Protein Atlas. We further evaluated the prognostic value of ZNF671 expression among numerous cancer types using the “Kaplan–Meier plotter” (KM plotter) database. We found that downregulation of ZNF671 is associated with hypermethylation of its promoter. Survival analysis established that the downregulation of ZNF671 predicts poor prognosis in breast invasive carcinoma (BRCA), cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), head and neck squamous cell carcinoma (HNSC), kidney renal papillary cell carcinoma (KIRP), lung adenocarcinoma (LUAD), pancreatic adenocarcinoma (PAAD), and uterine corpus endometrial carcinoma (UCEC) solid tumors. CCK-8 and Transwell functional assays showed that ZNF671 could inhibit tumor cell proliferation, migration, and invasion. These results indicate that ZNF671 is an excellent predictive factor for BRCA, CESC, HNSC, KIRP, LUAD, PAAD, SARC, and UCEC solid tumors and may play crucial roles in the development and progression of these tumors.